The social and political ideas of the muckrakers - Chalmers, David Mark 1927- (Essay Index reprint series, 1964)
During the first decade of the twentieth century, a small group of professional journalists flooded the popular magazines with detailed exposés of the corruption that had accompanied the growth of industry and the development of a business society in the United States. They examined almost all aspects of American life and paved the way for the reforms of the Progressive Era. This book carefully studies what each one had to say. All of them developed definite explanations for the crisis, and each of them suggested what might be done about it. The free institutions of the nation were being menaced by the growth of concentrated economic power and the spreading web of commercialism which came with it. The journalists agreed that the fault came from the fact that the profit motive had become enthroned in America and business had become the dominant national institution, because the development of corporate wealth-seeking had outstripped the national legislative and moral awareness. Out of their work emerges a fascinating picture of American life during the turn of the century and the First World War.--From publisher description.